"It is not something that has been discussed": Climate change in teacher education in Greenland and Canada. Issue 2 (3rd April 2021) - Demant-Poort, Lars; Berger, Paul
Abstract: We describe findings from an exploratory study on Greenlandic and Canadian preservice teachers' (PSTs') views on climate change teaching and teacher education programs. Greenland and Canada are experiencing more rapid warming than the global average. Climate resilience is thus of great importance and climate change needs to be taught to foster innovations and adaptation and to prepare young citizens to be engaged participants in policy debates about mitigation. Forty-five PSTs at the University of Greenland and Lakehead University answered a survey comprised mainly Likert Scale and open-ended questions. We found that PSTs need more knowledge about climate change, while, across disciplines, almost all would like to teach climate change and believe that preparing to do so should be a part of initial teacher education.